Diagnosis of abnormal uterine bleeding using PALM COEIN classification and its management: An institutional experience - Chandregowda, Chandana; Reddy, Swathi Aswath; Datti, Sujatha; Venkatesh, Shreedhar (Nepal Journal of Obstetrics and Gynaecology, 2021)
Aims: Categorization and treatment of abnormal uterine bleeding based on FIGO - PALM COEIN classification system Methods: A prospective cross-sectional observational study was conducted in the Department of Obstetrics and Gynaecology, Vydehi Institute of Medical Sciences and Research Centre, Bengaluru for a period of 1year from January 2019 to December 2019. All cases with abnormal uterine bleeding in 20 - 50 years of age were taken. Clinical details and imaging tests recorded, and categorized by FIGO- PALM COEIN classification for diagnosis and treatment. Statistical Package for Social Sciences version 21 was used to analyse the data and presented as frequencies and percentages. Results: Out of 300 women of AUB, 190 had structural (PALM) and 110 women had nonstructural (COEIN) aetiology; 138 women among 300 underwent hysterectomy and 20 patients underwent hysteroscopic polypectomy. Levonorgestrel intrauterine device inserted in 40 patients, 85 women were managed medically and 17 women lost to follow-up for further management. Conclusion: FIGO PALM-COEIN classification system for the diagnosis and treatment of abnormal uterine bleeding was adopted for the uniform standard.